2022
DOI: 10.1186/s41016-022-00304-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic surgery versus craniotomy in the treatment of spontaneous intracerebral hematoma: a systematic review and meta-analysis

Abstract: Background Spontaneous intracerebral hemorrhage (SICH) has high morbidity and mortality, with no clear standard of treatment available. Compared with the craniotomy approach, neuroendoscopy is a relatively minimally invasive treatment method, and may be an efficient alternative. Therefore, this meta-analysis aimed to assess the clinical efficacy of neuroendoscopy and craniotomy in SICH patients. Methods The electronic databases Web of Science, PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Otherwise, the solo application of a surgical microscope was and is still the best aid to maximize the excision of intracranial tumours. However, the microscopic view is limited to direct co-axial vision and poor illumination due to a divergent light beam from the overhead operating room light source (Du et al, 2022). The deeper the dissection lesser is the illumination of a tumour workpiece to both aided and unaided eyes of a surgeon.…”
Section: Status Of Neuro-endoscopementioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, the solo application of a surgical microscope was and is still the best aid to maximize the excision of intracranial tumours. However, the microscopic view is limited to direct co-axial vision and poor illumination due to a divergent light beam from the overhead operating room light source (Du et al, 2022). The deeper the dissection lesser is the illumination of a tumour workpiece to both aided and unaided eyes of a surgeon.…”
Section: Status Of Neuro-endoscopementioning
confidence: 99%
“…Undoubtedly, the better illumination and wider view of hard-to-access sites with an endoscope are resulting in near complete resection of tumour tissue (Singh et al, 2018;Tammam et al, 2022). In the last decade, there have been several studies, including systematic reviews and meta-analyses, which have shown extremely favourable outcomes where a neuro-endoscope has been combined with a microscope (Du et al, 2022;Sayehmiri et al, 2022;Tan et al, 2022). It has helped not only to increase the volume of removed tumour tissue but also reduced operative time, intra-operative complications and post-surgical neurological deficits, and tumour recurrence (Barber et al, 2013;Rigante et al, 2019;Singh et al, 2018;Tammam et al, 2022).…”
Section: Status Of Neuro-endoscopementioning
confidence: 99%